Nonresonant third-order nonlinearity of antimony glasses at telecom wavelengths - Gomez, Luis A.; de Araujo, Cid B.; Messias, D. N.; Misoguti, L.; Zilio, S. C.; Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2006)
We report measurements of the nonresonant nonlinear refractive index n(2) in antimony glasses at telecom wavelengths. The measurements were performed using the Z-scan technique with a 130 fs pulsed laser operating at five wavelengths in the range of 1400-1600 nm. Values of n(2)approximate to 10(-15) cm(2)/W were measured and a negligible two-photon absorption coefficient (< 0.003 cm/GW) was estimated for all glasses compositions. The samples present a good figure of merit for ultrafast all-optical switching. (c) 2006 American Institute of Physics.